The Propulsion Path of Synergy and Linkage Based on Artificial Intelligence and Digital Economy - Wu, Yan; Zhu, Yuqin; Zhao, Jingfeng (Frontiers in Psychology, 2022)
From conception to birth, artificial intelligence inherited the power of human reproduction, such as creativity, self-improvement and language use, etc. These abilities cannot be exercised in other places. The purpose of this paper is to explore the path of collaborative promotion based on artificial intelligence and digital economy. First, it outlines the scattered use of data by individuals at the two application levels of the digital economy and the systematic use of data by enterprises on large organizations. In this study, artificial intelligence and digital economy are introduced into the ability of project information sharing in the field of the enterprise project, and then their important role in improving the performance of enterprise project management is analyzed. Secondly, try to use interviews, scale analysis and logical subtraction to formulate the measurement standards of the digital environment and project information publishing ability, and provide basic data for follow-up research. The experimental results show that 54% of middle-level personnel said that the synergy between enterprise artificial intelligence and digital economy is very good, and they have a positive attitude towards exploring new ways to promote digital economy integration in the field of artificial intelligence.